MARKETING MIX ANALYSIS OF THE ATTRACTIVENESS OF PENGLIPURAN TOURISM VILLAGE - I Putu Ryan Dharma Putra; Firlie Lanovia Amir (LPSDI Bina Patria, 2024)
The development of tourism, especially in tourist villages in Bali, has experienced a very significant increase. This can be seen from the development of tourist villages which is increasing over time. The development of tourist villages is also one of the main programs being developed by the Bali government. The development of tourist villages in the long term is also caused by the increasing negative impacts produced by mass tourism. So that the resulting negative impact causes a shift in the trend of tourists visiting tourism destinations towards alternative and quality tourism. So, in order to increase the existence of the tourist attraction of the Penglipuran Tourism Village, other aspects are needed to support the development of the existence of a tourist destination. In collecting data, researchers carried out three basic stages, including observation, interviews and literature study. Observe first by identifying problems directly at the research location, namely Penglipuran Tourism Village. Tri Hita Karana is a concept in Balinese culture that refers to three main principles that underlie prosperity and harmony in life. These principles include the relationship between humans and God, humans and other humans, and humans and nature. In analyzing the marketing mix of Penglipuran Tourism Village, it is important to ensure that all these elements work together to create a unique and valuable experience for tourists. Village managers must continue to improve and update their marketing strategies to ensure sustainable attraction and responsible tourism growth.